The effects of digital game-based instruction, teacher instruction, and direct focused written corrective feedback on the grammatical accuracy of English articles. Issue 4 (4th May 2021) - Reynolds, Barry Lee; Kao, Chian-Wen
Abstract: Feedback researchers have given little attention to how administration of language-focused instruction before writing in a second language combined with subsequent error correction after writing can affect the grammatical accuracy of learners' future writing. Moreover, the mode of the instruction (i.e., teacher instruction or game-based instruction) has also been undervalued. To address these gaps in the research literature, Taiwanese university student participants ( n = 45) were randomly and equally divided into two experimental and one control group: teacher instruction with error correction ; digital game-based instruction with error correction ; and error correction only . Participants were asked to write three letters of application to three similar job advertisements as a pretest, immediate posttest, and delayed posttest. Gain score results in the immediate posttest showed that the teacher instruction with error correction group significantly outperformed the error correction only group whereas gains in the delayed posttest showed the teacher instruction with error correction and the digital game-based instruction with error correction groups significantly outperformed the error correction only group. Results indicate that pedagogical practices that provide focused grammatical instruction with direct focused feedback are more beneficial to L2 writers than only providing error correction. Furthermore, the just-in-time grammar feedback provided during game play afforded learners with opportunities to engage in awareness-raising language related episodes. Such game play combined with written corrective feedback resulted in stronger retention of grammatical knowledge compared to learners that received teacher instruction combined with written corrective feedback.